German unification and its impact on net savings - Siebert, Horst (Inst. für Weltwirtschaft, 1993)
Lit.
Literaturverz. S. 17 - 19
Keywords: Graue Literatur; Sparen; Leistungsbilanz; Öffentliche Schulden; Zins; Wechselkurs; Nationale Einheit; Schock; Deutschland; Wiedervereinigung; Vereinigung; Wirtschaftliche Integration; Integration; Wirkung; Zahlungsbilanz